Further studies on the constituents of the gorgonian octocoral Pseudopterogorgia elisabethae collected in San Andre´s and Providencia islands, Colombian Caribbean: isolation of a putative biosynthetic intermediate leading to erogorgiaene (2006)
Chemical investigations of the MeOH–CH2Cl2 extract of Pseudopterogorgia elisabethae specimens collected in the islands of San Andre´s and Providencia, Colombian Caribbean, yielded four new diterpenes (1, 3, 5, 7) along with seco-pseudopterosin J (8), and amphilectosins A (9) and B (10). The structures of the new compounds were established through spectral studies as an elisabethatriene analog named elisabethatrienol (1), 10-acetoxy-9-hydroxy- and 9-acetoxy-10-hydroxy-amphilecta-8,10,12,14-tetraenes (isolated as an interconverting mixture) (3), amphilecta-8(13),11,14-triene-9,10-dione (5), and a seco-pseudopterosin 7-O-a-L-fucopyranoside named secopseudopterosin K (7). Elisabethatrienol can be regarded as a biosynthetic intermediate leading to erogorgiaene.